Digital Supply Chain for Revenue Collection of the Revenue Department in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
An academic article about digital supply chain  for Revenue Collection of the Revenue Department in Thailand aim to present tax management through a supply chain applying for better effective tax management The tax management needs to be appropriate to changes of globalized economy and society. The processes consisted of Suppliers,  The revenue department , Customers , consumers Satisfaction and feedback .All element connect with digital in the Thailand with the supply chain. This truly added the revenue department in Thailand .The supply chain will be applicable for Revenue Collection of the Revenue Department in Thailand.